Integrating Z-Score and GIS-Based Methods for Road Accident-‎Prone Segment Identification - Budhi, Wahyu Satyaning; Wari, Wahyu Naris; Amin, M. Shofi'ul; Utanaka, Ahmad; Widyastuti, Hera (International Journal of Basic and Applied Sciences, 2025)
The rapid development of road infrastructure today presents significant challenges in ensuring road safety. The National Road III section ‎from Kabat to the Banyuwangi City Boundary has shown a concerning trend in traffic accidents, highlighting the need to identify accident ‎locations. This study employed secondary data obtained from the Banyuwangi Police traffic unit accident reports. The research analysis was ‎conducted in two phases. First, the Z-score method was utilized to identify accident road segments through statistical evaluation. Subsequently, Hotspot Analysis (Getis-Ord Gi*) integrated with Geographic Information System (GIS) was applied to map and verify the spatial ‎clustering of accidents. Both methods consistently identified two critical segments out of 25 road sections (each 200 meters in length). These ‎were located at STA 5+200 – 5+400 with a 95% risk level and STA 8+400 – 8+600 with a 90% risk level, while the remaining segments ‎did not show statistically significant clustering of accidents. The consistency of results across both methods strengthens the reliability of the ‎findings, underscoring the importance of targeted safety interventions and accident mitigation strategies in these high-risk zones.